The perceived risks that influence the intention of consumers to do online purchases in East Malaysia - Caroline Geetha B. Arokiadasan; Kai Sheng Chin; Fennie Iswarnie Binti Bachok; Woan Lin Kong; Hui Xuan Liew; Ming Fook Lim (Penerbit Universiti Malaysia Sabah, 2021)
The purpose of this study is to investigate the perceived risks that influence the intention of consumers to do online purchase in East Malaysia. The researchers adopted the Theory Planned behavior (TPB) in this study, followed by the independent variables (financial risk, product risk, security risk, time risk, social risk, and psychological risk), and dependent variable (intention of consumers to do online purchase) respectively, to achieve the study’s objectives. In this case, the researchers applied convenience sampling, which involved selecting samples based on the volunteers’ flexibility and readiness to complete the survey. Considering the time issue, the researchers can only collect 140 respondents as the primary data. These data are obtained from the Google Form questionnaire for citizens with online shopping experience in East Malaysia. After that, the researchers exported the data to the 27th edition of the Statistical Package for Social Science (SPSS) for analysis. In short, there are four analyses that was run by the researchers, namely factor analysis, reliability analysis, descriptive analysis for demographic profile, and regression analysis. The result of the reliability analysis indicated that the questionnaire was a reliable instrument to measure the objectives of this study. On the other hand, regression analysis has been done and the result showed all of the hypotheses in this study were accepted where all of dimensions in perceived risks have influence the intention of consumers to do online purchase in East Malaysia.